Can Agroforestry Farmers Attain Sustainability? Case of Farmers in Selected Upland Farming Communities in the Philippines - Leila Dimayuga Landicho; Josefina T. Dizon; Agnes C. Rola; Maria Ana T. Quinbo; Rowena DT. Baconguis (International Journal of Agriculture System, 2017)
This article is based on the study which investigated the socioeconomic and biophysical conditions of the upland farming communities in the Philippines; identified the development pathways that were undertaken by the upland farmers; and determined level of sustainability of the upland farming communities on the basis of their development pathways. This article argues that agroforestry farmers in upland farming communities in the Philippines can attain sustainability. This argument is based on the study conducted in the three pilot upland communities of the Conservation Farming Villages program in Albay, Ifugao and Negros Oriental, Philippines. From seven focus group discussions (FGDs) with at least 12 participants per FGD for a total of 147 farmers, and farm household survey of 230 upland farmers, research results indicate that agroforestry farmers in the three study sites were smallholders and were cultivating in areas with marginal conditions. There were five development pathways identified. These are monocropping in contour, multiple cropping in contour, agroforestry, agroforestry with non-farm activities, and multiple cropping/monocropping without contour. With the community capitals framework as the theoretical foundation, analysis indicated that the five development pathways contributed to a high level of social, human and political capitals having mean scores of 0.73, 0.55 and 0.54, respectively; a moderate level of physical, financial and natural capital, with mean scores of 0.23, 0.20 and 0.23, respectively; and a very low level of cultural capital with mean score of -0.08. At the community level, on the other hand, research results revealed that the CFV sites in Ligao, Albay and La Libertad, Negros Oriental have almost similar contributions to the sustainability of the upland farming communities, while Alfonso Lista, Ifugao had the lowest. Thus, institutional arrangements with the farmers’ association and the local government units also played a key role in the sustainability of the upland farming communities. These results imply the need for a holistic and collaborative engagement towards attaining sustainable upland farming communities.